Pseudoprecocious puberty due to functional cystic juvenile granulosa cell tumor of the ovary in a 5-year-old girl - Shailaja Prabhala; Jayashankar Erukkambattu; Karthikbabu Perumalla; Annapurna Srirambhatla; Ramamurti Tanikella (Wolters Kluwer Medknow Publications, 2016)
A 5-year-old girl child presented with features of pseudoprecocious puberty in the form of bleeding per vaginum and bilateral breast enlargement since 10 days. The radiological imaging showed a right ovarian cyst and the biochemistry revealed elevated estradiol. With a provisional diagnosis of functioning ovarian lesion, a right-sided ovarian cystectomy and ovariotomy was performed, which showed features of cystic juvenile granulosa cell tumor.